THE INFLUENCE OF INTERNAL AND EXTERNAL FACTOR TO THE CAPITAL STRUCTURE AND FIRM’S FINANCIAL PERFORMANCE : EVIDENCE FROM PROPERTY AND REAL ESTATE SECTOR LISTED IN INDONESIA STOCK EXCHANGE 2010-2012 - Karima, Tsabita; Suhadak, Suhadak; Handayani, Siti Ragil (FIA UB, 2014)
This research is performed in order to test the relationship between internal and external factor on capital structure and financial performance in property and real estate sector listed in IDX. Unit of analysis consists of 26 companies. Analysis shows that Internal Factor has negative significant influence on Capital Structure and External factor has negative influence on negative effect of capital structure. Besides, better internal factor (Liquidity and firm size) did not make the financial performance of property and real estate companies listed on the IDX become good. This study precisely shows that the test result is insignificant between the internal factor and financial performance which was measured by ROE. The test results, as well as the relationship between external factor and financial performance, have insignificant influence and the last hypothesis testing shows that Capital structure has positive significant influence on financial performance of property and real estate companies listed on the IDX. Â Key words: internal factor, external factor, capital structure, financial performance.